A Upaya Peningkatan Hasil Belajar Peserta Didik Kelas IV SD Negeri Seworan Materi Hubungan Antargaris melalui Pendekatan Realistic Mathematics Education (RME) dengan Media Konkret - Sri Hartati (Universitas Muhammadiyah Bangka Belitung, 2019)
This research is motivated by the learning of the conventional approach which is to provide packaging of ready-made material, students just need to receive, memorize, tend to be passive, teacher-centered, teachers tell a lot. abstract and theoretical,, so that learning outcomes are low. Through the application of the Realistic Mathematics Education (RME) approach, this problem is attempted to be improved and improved. The purpose of this study is to improve the learning outcomes of grade IV students of SD Negeri Seworan inter-line relationship material through the Realistic Mathematics Education (RME) approach of two cycles. Steps in each cycle consists of four stages, namely planning, acting, observing, and reflecting. The activities are collecting data by observing activities in the learning process, interviewing to obtain more complete data. Reality Mathematics Education (RME) percentage of pre-cycle learning completeness 41.67% to 58.33% in the first cycle increased 16.66 points, and to 91.67 in the second cycle increased 33.34 points. The average value of pre-cycle classes 58, 08 to 67.17 in the first cycle increased 9.09 points, and to 82.25 in the second cycle increased by 15.08 points. Student learning activeness in the pre-cycle learning process 47.87% criteria Good Enough, reached an average of 70.13% good criteria in the first cycle, increased 34.87 points and increased to 89.52 very good criteria in the second cycle increased 19, 39 points. The Realistic Mathematics Education (RME) approach can improve the learning outcomes of fourth-grade students in Semester 2 Elementary School, Seworan Wonosegoro Boyolali, material between relationships